PRETRIAL JUDGE AUTHORITY IN ADJUDICATING ADMINISTRATIVE ACTIONS CARRIED OUT BY THE DIRECTORATE GENERAL OF CUSTOMS - Erdianto Effendi; Rena Yulia (Universitas Lampung, 2023)
The Directorate General of Customs and Excise has administrative and law enforcement authority. In practice, judges often understand administrative authority as an investigative authority, thus granting pretrial requests for Acts that are the administrative authority. The method used is normative legal research is descriptive qualitative with qualitative analysis techniques using primary, secondary, and tertiary legal materials. The results showed that pretrial judges differed in interpreting administrative authority. Only two of the five judges interpreted administrative authority as not pretrial objects. Supposedly, judges are not authorized to examine the administrative authority exercised by Customs and Excise. Recommendations This research is to minimize the expansion of interpretation of the authority of forced efforts so that the issuance of the Supreme Mahakamh Circular or revise the Customs and Excise Law.